Grow Strategy: Training-Development of Drawing Competencies of Mis Al-Hilal Dender Banda Neira Teachers with Kosa Rupa - Alhail, Hadi; Rahmawati, Layung; Gardila, Bunga; Raisyabilla, Rangga Octava; Hayundaka, Anandam; Sasea, Sanita Carolina; Muhladin, Hildan; Kilwarani, Sigit (Gorga : Jurnal Seni Rupa, 2025)
Difficulties in demonstrating drawing-related learning pose a challenge for teachers at Madrasah Ibtidaiyah Swasta (MIS) Al-Hilal Dender. This study aims to develop teachers' competencies in drawing and Colouring at MIS Al-Hilal Dender, Banda Neira, using kosa rupa as a visual aid. This medium serves as a teaching tool to enhance teachers' creativity and skills in delivering visual arts education at the elementary school level. The research adopts a qualitative case study approach, involving three teachers as primary participants. The training was conducted using the GROW Coaching Model strategy, which consists of four stages: goal, reality, options, and will. In the goal stage, teachers formulate their learning objectives for drawing and Colouring. The reality stage identifies the teachers’ initial drawing skills before training. The options stage explores alternative solutions through mentoring and training using kosa rupa. The final stage, will, focuses on implementing the training outcomes in classroom instruction. The findings indicate a significant improvement in teachers’ drawing and Colouring abilities after the training. Evaluation was conducted based on composition, perspective, and Colouring aspects, showing an increase in scores from the initial to the final stage. Teachers’ responses to kosa rupa as a teaching medium were overwhelmingly positive, with increased confidence in delivering visual arts lessons. This study affirms that incorporating kosa rupa within the GROW Coaching Model strategy can be an effective method for enhancing elementary school teachers’ visual arts competencies. It is hoped that this approach can be widely implemented to support teacher development across various regions.